Becoming a speaker of multiple languages: an investigation into UK university students' motivation for learning Chinese. Issue 2 (4th March 2023) - Mayumi, Kayoko; Zheng, Ying
ABSTRACT: This study explored the language learning motivation of a small group of five university students in the UK through the constructs of Dornyei's L2 Motivational Self System and Henry's notion of 'the ideal multilingual self'. The five participants, all successful language learners at school, chose to specialise in modern languages at university and in addition to the foreign languages they had previously learned, decided to study Chinese. Interviews were conducted in the final year of the participants' university course and their motivational changes during the course of studying Chinese were explored. The results revealed that two students who achieved remarkable success in learning Chinese came to possess a strong desire to integrate in Chinese society, linked to a longer period spent studying in the target language country. We suggest that integrative orientation is a significant component in maintaining the ideal L2 self, especially when a psychological and physical distance exists in relation to the target language, its culture and the country.